Między nieklasyczną narracją i klasyczną dramaturgią. "Taki pejzaż" Jagody Szelc - Rojek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Between Classical Narration and Non-classical Dramaturgy. Jagoda Szelc’s Such a Landscape An abandonment of classical narration and a search for unconventional dramaturgical techniques are increasingly observed in the works of students from the Łódź Film School. One such short fi lm illustrating this tendency is Such a Landscape, directed by Jagoda Szelc. To create her individual and original piece, the director employs three traditional dramatic structures – that of an episodic fi lm, a Greek tragedy, and one connected with using the symbol as a tension-building tool. Jagoda Szelc proves that being sceptical about classical narration does not have to indicate a rejection of the whole tradition of storytelling. Instead, she chooses to use it as a fabric.